2014
DOI: 10.1590/s0100-736x2014001200013
|View full text |Cite
|
Sign up to set email alerts
|

Identification of canine papillomavirus type 1 (CPV1) DNA in dogs with cutaneous papillomatosis

Abstract: Canine oral papillomavirus (COPV), also known as Canine Papillomavirus type 1 (CPV1), induces papillomas at the mucous membranes of the oral cavity and at the haired skin of dogs. The classification of Papillomavirus (PV) types is based on the L1 capsid protein and nucleotide sequence; so far, 14 CPV types have been described in several countries, but the molecular characterization of CPV in Brazil is lacking. This study investigated the presence of the PV in seven papillomas from four mixed breed dogs from Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
1
3
0
2
Order By: Relevance
“…The putative variants CPV1UFSBR‐01 to 07 and CPV1UFSBR‐09 had the same mutations in the L1 partial gene sequences. All dogs presented with similar clinical and histopathological profiles with oral and cutaneous exophytic lesions, mostly in young mixed breed dogs, which were similar findings to a previously study in southern Brazil …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The putative variants CPV1UFSBR‐01 to 07 and CPV1UFSBR‐09 had the same mutations in the L1 partial gene sequences. All dogs presented with similar clinical and histopathological profiles with oral and cutaneous exophytic lesions, mostly in young mixed breed dogs, which were similar findings to a previously study in southern Brazil …”
Section: Discussionsupporting
confidence: 89%
“…In addition, the isolate CPV1UFSBR‐08 was characterized as a putative new CPV1 variant, with 99.2% similarity to the reference sequence (NC_001619) (Table ). In the phylogenetic tree, all samples from this study were clustered with partial sequences (CPV1BRUEL1 and CPV1BRUEL2) from southern Brazil (Figure ) …”
Section: Resultsmentioning
confidence: 84%
“…Some studies have identified different isolates or their DNA sequences which differ from the CPV reference type genome; however, they did not discuss whether these isolates could be CPV variants or not, or their potential role in pathogenesis. For example, different isolates of CPV1 were identified in cases of dogs with oral and cutaneous lesions in Turkey and Brazil (Alcântara et al, 2014;Oğuzoğlu et al, 2017;Reis et al, 2019). In Brazil, samples from different regions of the country have shown variants of CPV1 associated with oral and cutaneous lesions (Alcântara et al, 2014;Reis et al, 2019).…”
Section: Cancer -Squamous Cell Carcinoma (Scc)mentioning
confidence: 99%
“…For example, different isolates of CPV1 were identified in cases of dogs with oral and cutaneous lesions in Turkey and Brazil (Alcântara et al, 2014;Oğuzoğlu et al, 2017;Reis et al, 2019). In Brazil, samples from different regions of the country have shown variants of CPV1 associated with oral and cutaneous lesions (Alcântara et al, 2014;Reis et al, 2019). In one case of in situ oral SCC in a dog from Brazil, a new CPV1 variant was identified, showing the importance of studies that focus on the discovery of CPV variants that may influence the disease and could be associated with cases of cancer (Reis et al, 2019).…”
Section: Cancer -Squamous Cell Carcinoma (Scc)mentioning
confidence: 99%
“…Os papillomavírus são um grupo de DNA vírus que induzem lesões benignas e malignas em mucosas e epiderme, mais comumente em cavidade oral e lábios, ocorre em mamíferos e aves, e já foi descrita pela literatura a evolução para carcinoma de células escamosas em cavidade oral de cães. Existem vários tipos de papilomavírus, e eles são classificados com base na sequência de nucleotídeos L1 (DE ALCÂNTARA et al 2014).…”
Section: Papiloma Vírus Caninounclassified